2019
DOI: 10.1038/s41467-019-08491-9
|View full text |Cite
|
Sign up to set email alerts
|

A number-based inventory of size-resolved black carbon particle emissions by global civil aviation

Abstract: With the rapidly growing global air traffic, the impacts of the black carbon (BC) in the aviation exhaust on climate, environment and public health are likely rising. The particle number and size distribution are crucial metrics for toxicological analysis and aerosol-cloud interactions. Here, a size-resolved BC particle number emission inventory was developed for the global civil aviation. The BC particle number emission is approximately (10.9 ± 2.1) × 1025 per year with an average emission index of (6.06 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…If real aircraft aggregates behave like the propane flame soot studied here, the enhanced ice nucleation activity of such soot particles resulting from contrail processing could impact subsequent cirrus cloud formation. The caveat here is that the majority of aircraft emitted soot aggregates have diameters around 30 nm (Moore et al., ; Zhang et al., ). There is, however, some observational evidence of larger soot aggregates associated with aviation emissions (Petzold et al., ) and from contrail residuals (Petzold et al., ; Twohy & Gandrud, ).…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…If real aircraft aggregates behave like the propane flame soot studied here, the enhanced ice nucleation activity of such soot particles resulting from contrail processing could impact subsequent cirrus cloud formation. The caveat here is that the majority of aircraft emitted soot aggregates have diameters around 30 nm (Moore et al., ; Zhang et al., ). There is, however, some observational evidence of larger soot aggregates associated with aviation emissions (Petzold et al., ) and from contrail residuals (Petzold et al., ; Twohy & Gandrud, ).…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…The median values of the total and non-volatile particle number EIs listed in Table 4 of Moore et al (2017a) were calculated to be 3.4×10 16 and 1.9×10 15 kg-fuel -1 , which were comparable to the median values of the total and non-volatile EI(N10) from our measurements. Zhang et al (2019) reported an average nonvolatile particle number EI (diameter >10 nm) of 6.06×10 14 kg-fuel -1 for various conditions of engine thrust. The average value from Zhang et al (2019) is significantly smaller than the median non-volatile particle number EIs from Moore et al…”
Section: Particle Emission Indices For Take-off Plumesmentioning
confidence: 99%
“…Secondly, non-volatile particles, which are assumed to be equivalent to soot or BC particles, primarily have sizes in the range larger than ~10 nm (geometric mean diameter (GMD) of ~20-50 nm) under various operating conditions, with largest GMDs under ~100% engine-thrust conditions (Petzold et al, 1999;Lobo et al, 2015aLobo et al, , 2015bDurdina et al, 2019). Zhang et al (2019) recently proposed a global-scale aviation emission inventory for BC particles by integrating existing datasets of non-volatile particle emission indices (EIs).…”
Section: Introductionmentioning
confidence: 99%
“…The inventory provides new data for assessing the aviation impacts. More details about the emission inventory can be found in our recent article (Zhang et al, 2019). 3 Emission at Zurich Airport At the airport scale, the emission is normally estimated using the ICAO default LTO cycle.…”
Section: Nonvolatile Particle Number Emission Inventorymentioning
confidence: 99%
“…As a preliminary study, here we utilized the scheduled flight data from Official Aviation Guide (OAG) in conjunction with the International Civil Aviation Organization (ICAO) engine emission databank (ICAO, 2019) and our proposed nonvolatile particle number emission estimation method (Zhang et al, 2019)…”
Section: Emission Estimationmentioning
confidence: 99%